The Effect of Egocentric Taste Judgments on Stereotyping of Welfare Recipients and Attitudes Toward Welfare Policy. Issue 1 (January 2020) - Shepherd, Steven; Campbell, Troy
Despite the centrality of purchasing behavior and choice to the welfare debate, research has generally understood attitudes toward welfare at a broader level and as a function of rational or deliberative processes (e.g., self-interest, ideology). This project identifies the effect of egocentrism on welfare attitudes, finding that a welfare recipient's purchase of an item that the participant personally values less (vs. more) leads to increased stereotyping of welfare recipients (e.g., irresponsibility, impulsivity) and favorable attitudes toward policy that would restrict that purchase. This effect is illustrated for both chronic and situational preferences and across a number of products commonly debated in welfare policy. The authors find that egocentrism is robust to debiasing; therefore, tests of boundary conditions involved countering the stereotype of irresponsibility rather than the bias itself. For example, the effects do not emerge in the context of healthy foods and necessities, nor when information suggests that the target consumer is otherwise responsible (e.g., budgeting, clipping coupons). Implications for policy and welfare advocacy are discussed. In general, these findings establish how personal preferences may shape attitudes toward marginalized consumers and related policy.